AQP2 Promotes Astrocyte Activation by Modulating the TLR4/NFκB-p65 Pathway Following Intracerebral Hemorrhage - Deng, Shuwen; Chen, Xiqian; Lei, Qiang; Lu, Wei (Frontiers in Immunology, 2022)
Microglial and astrocyte activation and related cytokine secretion play key roles in secondary brain injury following intracerebral hemorrhage (ICH). We assessed the role of aquaporin (AQP)2 in immune response after ICH. We prospectively collected data from 33 patients with ICH and analyzed the serum AQP2 levels in these patients and age-matched healthy controls. A correlation analysis was also performed between patient serum AQP2 levels and clinical factors. In the rat ICH model, double-fluorescence staining for glial fibrillary acidic protein (GFAP) and AQP2 was performed to investigate the relationship between astrocytes and AQP2. Relative mRNA expression levels of GFAP and AQP2 were also measured. In the rat astrocyte cell line CTX-TNA2, toll-like receptor (TLR)4/nuclear factor kappa B (NFκB)-p65 pathway activation and GFAP levels were measured. The indirect influence of AQP2 on microglial polarization was assessed following exposure to the medium of astrocytes treated with AQP2-overexpression plasmid or silencing RNA. We found that the serum AQP2 expression was lower in patients with ICH. Sex and blood neutrophil count influenced serum AQP2 concentrations in patients with ICH on admission. Lower serum AQP2 levels were inversely correlated with 90-day Modified Rankin Scale scores after ICH, but were not correlated with National Institute of Health stroke scale (NIHSS) scores on admission. AQP2 overexpression and localization in GFAP-labeled astrocytes were observed in rats. AQP2 overexpression induced astrocyte activation with GFAP upregulation via TLR/NFκB-p65 signaling pathway activation in the rat astrocyte cell line CTX-TNA2. Astrocyte activation promoted interleukin-1β secretion. The medium of AQP2-overexpression astrocytes promoted the pro-inflammatory M1 phenotype in the immortal rat (HAPI) microglial cell line. Therefore, serum AQP2 is negatively correlated with post-ICH prognosis and may be a marker of inflammation in early-stage ICH. AQP2 overexpression promotes astrocyte activation and pro-inflammatory secretion, affects astrocyte-microglia crosstalk, and indirectly induces microglial polarization, which may augment inflammation after ICH.